A comparison study on the deoxygenation of coal mine methane over coal gangue and coke under microwave heating conditions. (August 2015) - Guo, Xuan; Ren, Jun; Xie, Chuanjin; Lin, Jianying; Li, Zhong
Graphical abstract: Highlights: Microwave has great advantages of energy and time saving in CMM deoxygenation. Microwave pretreatment results in graphitization of carbonaceous materials. Coal gangue shows benefit in restricting CH4 decomposition compared to coke. Under optimal conditions, there is no residual oxygen and CH4 is less than 2.2%. Abstract: Microwave heating has great advantages in saving energy and time; in this study, it has been first successfully applied in the deoxidization process of coal mine methane (CMM), where carbon in coal gangue reacts with oxygen in CMM. Compared with traditional heating, microwave pretreatment resulted in rapid heating of coal gangue in CMM deoxygenation, which was attributable to the graphitization of carbonaceous materials. This prominent advantage of microwave heating can contribute to deoxygenation. In addition, deoxygenation effectiveness for both coke and coal gangue under microwave heating was investigated. It was discovered that coke acted as a catalyst to some extent to accelerate methane decomposition. However, this effect could be greatly restricted when coal gangue was used in the deoxygenation process because of its chemical inertness. Under optimal conditions (650 °C and 300 mL/min), there was no residual oxygen in the outlet gas, and methane loss was less than 2.2%.